Digital Forensics and Cyber Crime 4th International Conference, ICDF2C 2012, Lafayette, IN, USA, October 25-26, 2012, Revised Selected Papers - Rogers, Marcus; Seigfried-Spellar, Kathryn C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains a selection of thoroughly refereed and revised papers from the Fourth International ICST Conference on Digital Forensics and Cyber Crime, ICDF2C 2012, held in October 2012 in Lafayette, Indiana, USA. The 20 papers in this volume are grouped in the following topical sections: cloud investigation; malware; behavioral; law; mobile device forensics; and cybercrime investigations.
Cloud Investigations -- Malware -- Behavioral -- Law -- New Developments in Digital Forensics -- Mobile Device Forensics -- Cybercrime Investigations.
Keywords: Computer science; Computer security; Computers and civilization; E-commerce.; Computer Science; Systems and Data Security; e-Commerce/e-business.; Computers and Society; Electronic books